Critical role for mitochondria in B cell receptor-mediated apoptosis - Bouchon, Axel; Krammer, Peter H.; Walczak, Henning (European journal of immunology, 2000)
Antigen-induced apoptosis of B cells serves to deplete the immune repertoire of anti-self specificities leading to central and peripheral B cell tolerance. However, the mechanism of B cell receptor (BCR)-mediated apoptosis is widely unknown. By using the human Burkitt lymphoma cell line BL60 as a model system for human germinal center B cells we show here that BCR-mediated apoptosis requires transcriptional activity but, in contrast to activation-induced T cell apoptosis, is neither mediated via known death receptor systems nor does it involve initial activation of caspase-8. Moreover, during BCR-induced apoptosis cytochrome c release and mitochondrial permeability transition (PT) precedecaspase activation. Although caspase inhibition after BCR stimulation blocks cleavage of caspase substrates and DNA fragmentation it does not prevent mitochondrial PT, cytochrome c release and cell death. Thus, BCR-mediated apoptosis is initiated by the caspase-independent induction of mitochondrial PT resulting in release of cytochrome c and subsequent activation of caspase-9, downstream caspases and apoptosis.